(-4, 0), (0, 0)
Step-by-step explanation:
We would apply the equation of parabola in the vertex form:
y = a(x-h)² + k
vertex (-2, 20) represents (h, k)
y-intercept (0, 0) represents (x, y)
Inserting the above in the formula:
0 = a(0 - (-2))² + 20
0 = a(0+2))² + 20
0 = a(2)² + 20
0 = a(4) + 20
-20 = 4a
divide both sides by 4:
-20/4 = 4a/4
-5 = a
The equation becomes:
y = -5(x-h)² + k
y = -5(x+2)² + 20
To get the x-intercept, we would replace y with 0
0 = -5(x+2)² + 20
-20 = -5(x+2)²
-20/-5 = -5(x+2)²/-5
4 = (x+2)²
square root both sides:
![\begin{gathered} \sqrt[]{4}\text{ = }\sqrt[]{(x+2)^(2)} \\ \pm2\text{ = x+ 2} \\ x+2\text{ = }\pm2 \\ x\text{ = -2}\pm2 \\ x\text{ = -2 + 2 or -2 - 2} \\ x\text{ = 0 or x = -}4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3m2nvo82611y6y43pb2gxyuaa5uxewx7x8.png)
The answer in the form (x1,y1),(x2,y2) is (-4, 0), (0, 0)